The Relationship Between Hemoglobin Levels and Femoral Cartilage Thickness - Malas, Fevziye Ünsal; Öztürk, Gökhan Tuna (Acta Medica, 2014)
Objective: To explore the relationship between hemoglobin (Hb) levels and ultrasonographic (US) femoral cartilage thickness in healthy subjects. Methods: Thirty-eight women who were admitted to our outpatient clinic for musculoskeletal complaints other than knee joint problems were recruit- ed. Nineteen women (mean age: 34.6 ±7.3 years (22-43) and mean body mass index (BMI): 26.0 ±5.0 kg/m2) with Hb levels ≤12 g/dL and nineteen healthy women with Hb levels >12 g/dL were included in the study. Distal femoral cartilage thickness was measured from the mid-points of the right medial condyle (RMC), right lateral condyle (RLC), right intercondylar area (RIA), left medial condyle (LMC), left lateral condyle (LLC) and left intercondylar area (LIA) using US. Results: Subjects with low Hb levels (<12 g/dL) had thinner femoral cartilage thickness values at RMC (p = 0.001), at LMC (p = 0.008) and LIA (p = 0.017) when compared to those subjects with higher Hb levels (>12 g/dL). Conclusion: Lower Hb levels seem to have negative impact on the femoral cartilage thickness. Additional studies are necessary to provide a better in- sight into understanding the clinical relevance of our finding and whether anemia treatment can reverse this process